EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR KOLASE SISWA KELAS X SMA N 2 GUNUNG TALANG - Yeyen Efriyeni Viyasa; Ade Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning is a communication process in which information is conveyed from a source to a receiver for specific purposes. This study aimed to analyze the effectiveness of the Project Based Learning (PjBL) model on the collage learning outcomes of tenth-grade students at SMA Negeri 2 Gunung Talang. The problem identified in this study was the lack of student participation and the dominance of teacher-centered learning. This research employed a quantitative method with a quasi-experimental design, involving Class X E1 as the experimental group (34 students) and Class X E2 as the control group (35 students). Data were collected through pretests and posttests. The results of descriptive statistical analysis showed that the average posttest score of the experimental class (64.62) was higher than that of the control class (47.89). The Kolmogorov-Smirnov normality test indicated that the pretest and posttest data of both classes were normally distributed, with significance values greater than 0.05. The homogeneity test showed that the posttest data variances of both classes were homogeneous, with a significance value of 0.086 > 0.05. Furthermore, hypothesis testing using the t-test showed a Sig. (2-tailed) value of 0.001, which was lower than the alpha level of 0.05. Therefore, H₀ was rejected and Hₐ was accepted, indicating that the implementation of the Project Based Learning (PjBL) model improved students' learning outcomes in the Collage topic of the Cultural Arts subject for tenth-grade students at SMA Negeri 2 Gunung Talang.